The Social World, Reexamined : A Conversation with Brian Epstein. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and Brian Epstein, Associate Professor of Philosophy at Tufts University. Brian Epstein's career as a management consultant piqued his interest and his later research into the reasons why our current models of economics, politics and other areas of social science so often go terribly wrong. The conversation explores how we can dramatically improve our current economic and political models by reexamining our assumptions about the nature of the social world.This carefully-edited book includes an introduction, The Real Wo.